Shift in the Reproductive Strategies of Phragmites australis Under Combined Influences of Salinity and Tidal Level Changes - Yinhua Wang; Xin Lyu; Xinyi Tian; Changcheng Guo; Yifan Li; Chen Yang; Ningning Li; Hongyu Guo (Agronomy, 2025)
Understanding how clonal plants modulate their reproductive strategies under environmental fluctuations is critical for assessing their resilience amid rapid global change. Phragmites australis, a dominant clonal plant species in coastal wetlands worldwide, provides vital ecological and agricultural services. As coastal wetlands are currently impacted by sea level rise, P. australis faces both salinity and tidal level changes. However, the effects of the combined influences of these two abiotic factors on the reproductive strategy of P. australis remain unclear. We conducted a mesocosm experiment to examine how P. australis allocates resources between clonal and sexual reproduction under different salinity and tidal level conditions. We found increased salinity negatively impacted both sexual and clonal reproductive metrics and shifted reproductive allocation toward clonal reproduction; increasing tidal level had positive effects on the sexual reproductive metrics, but negatively affected the clonal reproductive metrics, leading to a shift toward greater allocation in sexual reproduction. Higher tidal levels could reduce the negative impact of salinity on the plant’s most reproductive metrics. These results highlighted the flexibility of P. australis in adapting its reproductive strategies to environmental changes, suggesting that it could be a promising component for sustainable wetland agriculture, offering significant economic value amid rapid global change.